Programa Vamos Cuidar do Brasil com Escolas Sustentáveis : análise de uma experiência na Escola Estadual Antonio Padilha no munícipio de Sorocaba-SP - Freitas, Maria Estela Maciel (2015)
Considering that the construction of sustainable social practices are central goals to guide the education of citizens in any learning context the Ministry of Education (MEC) has prepared the Progran “Let’s take care of Brazil” with sustainable schools which provides guidelines for the development of environmental education practices in schools. To participate in this program the school must present an ongoing project, addressing social and environmental issues in which the student is the subject of their learning in order to reach a personal, collective, conscious and critical training. Thus, among the objectives of this research are highlighted as follows: describe and analyze the development of the Program proposed by Ministry of Education (MEC) “Let’s take care of Brazil with sustainable schools / COM –VIDA” in school E.E. Antonio Padilha, located in Sorocaba-SP between the years 2013 and 2014, describe and analyze the practices developed by COM-VIDA and identify practices related to sustainability of those involved in the project. The methodology that leads this research is the study of qualitative case, as the case study focuses on a particular event revealing its peculiarities. For data collection were used different methods such as document analysis, participant observation, questionnaires and semi-structured interview. The Project began timidly in 2013 with the realization of practices that motivated students to participate in the IV National Children and Youth Conference for the Environment and as a result, we have the first group of students who started actions of environmental education at school. In 2014, such actions kept leading the construction of the COM-VIDA, a discussion space on environmental issues, providing carrying out actions to improve the quality of life and sustainability in the school environment. The implementation of the program and the construction of the COM-VIDA, provided to students of elementary school (6º to 9º years) practical experiences in environmental education focused on sustainability. The workshops COM-VIDA, guided in education for sustainability, the students had the opportunity to identify, discuss and propose solutions to local environmental and social problems. Among these activities are the awareness Project “Sustainability without being cliché” about the waste and proper disposal of garbage with the implementation of selective collection in our school, and growing food in the school garden. All activities were designed by the students themselves are the main protagonists in this process. Through these experiences for building theory knowledge about sustainability, it has been built their environmental identities. The move COM-VIDA has made the theme enter therein in the school environment both by students and by the managment staff causing small changes in individual and collective attitudes of the entire school community.